Descriptive characterization of Brazilian surfers and their injuries: a cross-sectional and retrospective study - Matheus Graciano Oliveira; Eduardo Takeuchi; Bruno Mezêncio; André Cavalcante Santos; Ana Paula da Silva Azevedo (Termedia Publishing House, 2024)
Purpose The present study aimed to describe the main characteristics of Brazilian surfers and their injuries, and to analyze the probability of developing injuries according to skill level, experience in surfing, training volume, and age. Methods A total of 1829 Brazilian surfers answered an electronic survey about their characteristics and previous and current injuries. The association between participant characteristics and percentage of injuries was investigated using a chi-squared test. The statistical significance of the results was assumed at a p -value < 0.05. The prevalence ratio (PR) was also calculated to illustrate the probability of having injuries. Results Most surfers are men (84.2%), young adults (72.0%), with more than 2 years of experience in surfing (60.7%), with an intermediate level of skill (49.3%), recreational surfers (99.2%), and who practice surfing 1 to 2 days a week (79.7%) for 1 to 3 hours a day (65.9%). About 55.5% of the participants were already affected by an injury or had some surfing-related pain. In the last 12 months, 52.2% of surfers suffered injuries. For both, more than 50% of injuries occurred in the lower limbs. Brazilian surfers with higher skill levels, time of experience, hours per day of surf training, and age presented higher prevalence ratios of previous and current injuries. Conclusions In summary, Brazilian surfers are predominantly male, young adults, and non-competitive athletes. The most injured anatomical region in this group is the lower limbs. Contrary to expectation, higher experience and skill levels might not act as protective factors against injuries due to increased training volume.